2015
DOI: 10.14260/jemds/2015/2357
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hematological Parameters as a Possible Marker for Head - And - Neck Cancer and Precancerous Conditions

Abstract: BACKGROUNDHead neck cancer (HNCA) is a major health problem, accounting for 30-40% cancers at all sites with the incidence in North-East India, where this study has been conducted is highest in the country (54.48%). As various substances alter quantitatively in the serum during tumor development, we intended to explore the changes in the haematological profile in cases of head neck squamous cell carcinoma and epithelial precursor lesions. Moreover, such study will be the first on HNCA patients in this North Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Whilst several studies have reported positive associations between MCHC and oral squamous cell carcinoma [ 80 ] or head and neck cancers [ 81 ], others found no statistically significant associations [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst several studies have reported positive associations between MCHC and oral squamous cell carcinoma [ 80 ] or head and neck cancers [ 81 ], others found no statistically significant associations [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…22 For other risk factors, such as p53 mutation, loss of heterozygosity (LOH), HPV, etc. 23 Claudia Cordilla in the study revealed hemoglobin status is associated with lymph node metastasis in squamous cell carcinoma of oral cavity but not with initial T stage. 24 Also, contrary to this study finding, Bhattacharjee et al showed statistically significant difference in hemoglobin value between squamous cell carcinoma of oral cavity and epithelial precursor lesion with the control.…”
Section: Discussionmentioning
confidence: 89%